MOLECULAR DETECTION OF FUSARIUM INFECTIONS IN WHEAT - A MEASURE OF QUALITY ASSESSMENT - Popescu, Sorina; Boldura, Oana Maria; Borozan, Aurica; Madosa, Emilian (Journal on Processing and Energy in Agriculture, 2022)
The aim of this paper was to evaluate 50 wheat samples collected from different western Romanian locations based on microbiological, molecular and toxicogen assays to determine their correlation when species of the genus Fusarium were analysed. The presence of toxins determined by biochemical ELISA (Enzyme-Linked Immunosorbent Assay), the DNA analysis based on PCR (Polymerase Chain Reaction) and even accurate species identification using specific gene sequencing were used to evaluate the fungal early infection,. Considering that in Romania the prevalence of Fusarium graminearum and Fusarium proliferatum infections is the most important, it can be stated that the screening with primers specific to fungal species ensures a preliminary test for fungal infection identification before performing the test for mycotoxins.